(untitled) (Indonesian Anti Corruption Studies, 2025)
Media literacy is increasingly recognized as a vital tool for empowering citizens to critically engage with information and foster anti-corruption awareness. This study investigates the relationship between media literacy levels and anti-corruption awareness among rural communities in Indonesia. Using mixed methods including surveys, focus groups, and participatory workshops, the research assesses how access to information and critical consumption of media influence perceptions of corruption and civic engagement. Results suggest that higher media literacy correlates with increased awareness of corruption issues and a stronger inclination toward participation in local accountability initiatives. The study highlights the potential of media literacy programs to support anti-corruption efforts in marginalized areas, where information asymmetry often undermines governance. This paper contributes to international discourse on the intersection of media, education, and corruption prevention in developing country contexts.